2020
DOI: 10.1007/s10571-020-00878-3
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Protects Blood-Spinal Cord Barrier Integrity by Modulating Microglia Polarization Through Activation of STAT3/SOCS3 and Inhibition of NF-кB Signaling Pathways in Experimental Autoimmune Encephalomyelitis Mice

Abstract: We previously reported that tetramethylpyrazine (TMP) alleviates experimental autoimmune encephalomyelitis (EAE) by decreasing glia activation. Activated microglia has been shown to mediate blood-spinal cord barrier (BSCB) disruption, which is a primary and continuous pathological characteristic of multiple sclerosis (MS). Therefore, in this study, we further investigated whether TMP protects the BSCB integrity by inhibition of glia activation to alleviate EAE. Extravasation of evans blue was used to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…83 Recently, microglia treated with tetramethylpyrazine, a drug that promotes M2 microglial polarization, were shown to preserve functional integrity of the blood-spinal cord barrier in a murine model of experimental autoimmune encephalomyelitis (EAE). 84 This is the first study to directly show that microglial cells with an anti-inflammatory phenotype can protect brain barriers against pathological stressors.…”
Section: Microglia Activation: M2 Anti-inflammatory Phenotype and Bbbmentioning
confidence: 96%
“…83 Recently, microglia treated with tetramethylpyrazine, a drug that promotes M2 microglial polarization, were shown to preserve functional integrity of the blood-spinal cord barrier in a murine model of experimental autoimmune encephalomyelitis (EAE). 84 This is the first study to directly show that microglial cells with an anti-inflammatory phenotype can protect brain barriers against pathological stressors.…”
Section: Microglia Activation: M2 Anti-inflammatory Phenotype and Bbbmentioning
confidence: 96%
“…Further, using a blocker of fibrinogen and microglial integrin receptor Mac-1, microglia-mediated vascular repair/maintenance was hindered. Another study looked to bias microglial polarization towards the M2 state using tetramethylpyrazine and found that TMP-treated M2 microglia through activation of STAT3/SOCS3 and inhibition of NK-κB promote blood-spinal cord barrier integrity in EAE mice [ 56 ]. Taken together, these studies demonstrate the importance of microglia in the maintenance and repair of the blood-spinal cord barrier.…”
Section: Role Of Microglia Following Scimentioning
confidence: 99%
“…When microglia are polarized to the M2 phenotype, they can better protect the blood-brain barrier by producing IL-10 and TGF- β 1, as well as VEGF, IL-8 and pro-MMP-9 to promote vascular remodeling ( Jiang et al, 2018b ). The use of tetramethylpyrazine (TMP) in experimental autoimmune encephalomyelitis animal models protects the blood-spinal cord barrier by activating the signal transducer and activator of transcription 3 (STAT3)/Suppressor of Cytokine Signaling 3 (SOCS3) signaling pathway and promoting microglia polarization from M1 to M2 phenotype ( Zhang et al, 2021b ). M1-type microglia not only secrete pro-inflammatory cytokines, but also secrete chemokines such as chemokine (C-C motif) ligand 2 (CCL2) and Chemokine C-X-C ligand 10 (CXCL10) to recruit more immune cells and compromise the integrity of the blood-brain barrier ( Jiang et al, 2018b ).…”
Section: Microglia In Strokementioning
confidence: 99%